2002
DOI: 10.1016/s0014-5793(02)02524-3
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and electron paramagnetic resonance analyses of nitrate reductase NarGH from a denitrifying halophilic euryarchaeote Haloarcula marismortui

Abstract: Genes encoding the NarG and NarH subunits of the molybdo^iron^sulfur enzyme, a nitrate reductase from a denitrifying halophilic euryarchaeota Haloarcula marismortui, were cloned and sequenced. An incomplete cysteine motif reminiscent of that for a [4Fe^4S] cluster binding was found in the NarG subunit, and complete cysteine arrangements for binding one [3Fe^4S] cluster and three [4Fe^4S] clusters were found in the NarH subunit. In conjunction with chemical, electron paramagnetic resonance, and subcellular loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…In general, the characteristics of these enzymes showed marked resemblance with the bacterial NarGH complex, underscoring the fact that there was a relevant difference related to the subcellular localization between the halophilic and bacterial enzymes (Yoshimatsu, Iwasaki, & Fujiwara 2002;Martinez-Espinosa et al, 2007).…”
Section: Respiratory Nitrate Reductases In Haloferax Genusmentioning
confidence: 91%
See 1 more Smart Citation
“…In general, the characteristics of these enzymes showed marked resemblance with the bacterial NarGH complex, underscoring the fact that there was a relevant difference related to the subcellular localization between the halophilic and bacterial enzymes (Yoshimatsu, Iwasaki, & Fujiwara 2002;Martinez-Espinosa et al, 2007).…”
Section: Respiratory Nitrate Reductases In Haloferax Genusmentioning
confidence: 91%
“…Haloarcula marismortui (Yoshimatsu et al, 2002), however, the its regulation has not been explored yet.…”
Section: Genes Coding For the Enzymes Sustaining Denitrificationmentioning
confidence: 99%
“…Recently, the similarity of Nar to selenate reductases has also been indicated on the basis that both enzymes have Asp ligands to the Mo atom (Jormakka et al, 2004). In addition, the N-terminal region of NarG includes a typical twin-arginine signal peptide for protein translocation across the membrane by the Tat export pathway and the enzyme has activity in situ with both membranepermeable benzyl viologen and membrane-impermeable methyl viologen, suggesting that the catalytic site is located in the outside of the membrane, as described for the T. selenatis selenate reductase (Yoshimatsu et al, 2002). In contrast, bacterial NarG faces the cytoplasmic side of the membrane and nitrate reduction takes places in the cytoplasm (Berks et al, 1995;Moreno-Vivián et al, 1999).…”
Section: Respiratory Nitrate Reduction In Archaeamentioning
confidence: 97%
“…The enzyme was first described as a homotetramer of a 63 kDa polypeptide (Yoshimatsu et al, 2000), but further characterization revealed that it is a heterodimer with 117 and 47 kDa subunits, the 63 kDa band being an incomplete denaturation state of the enzyme (Yoshimatsu et al, 2002). It has been proposed that the H. marismortui Nar is a new archaeal type of membranebound nitrate reductase (Yoshimatsu et al, 2002). First, the enzyme is composed of two subunits, which are homologous to the NarGH bacterial subunits, but lacks the NarI membrane-associated protein.…”
Section: Respiratory Nitrate Reduction In Archaeamentioning
confidence: 99%
“…Organisms from all three domains of life are capable of carrying out this process. In addition to the experimentally characterized nitrite reductase (NirK) and nitrate reductase (NarGH) in H. marismortui (Yoshimatsu et al 2000(Yoshimatsu et al , 2002Ichiki et al 2001), the genome analysis identified at least four additional proteins with functions important for denitrification, viz. a nitrilase, a carbon-nitrogen hydrolase involved in reduction of organic nitrogen compounds and ammonia production; an ammonia-dependent NAD synthetase; a dissimilatory nitrate reductase; and an ammonium transporter.…”
Section: The Integrated Annotation and Network Discovery Approach Impmentioning
confidence: 99%